Edukasi Krim Berbahaya Mengandung Merkuri & Cara Cek BPOM pada Siswa Siswi SMAN 1 Alalak - Yulianita Pratiwi Indah Lestari; Dina Azizah; Dhea Indah Cahyani; Dita Putri Aulia (Yayasan Literasi Sains Indonesia, 2023)
Excessive attention to aesthetic skin problems, the widespread use of cosmetics by the public with all the positive and negative impacts received by the skin, have also brought developments in medical science in general, in the field of Dermatology in particular. The purpose of carrying out community service activities in the form of counseling about